The Anatomic Features and Role of Superficial Inferior Epigastric Vein in Abdominal Flap - Park, Seong Oh; Imanishi, Nobuaki; Chang, Hak (Archives of Plastic Surgery, 2022)
In lower abdominal flap representing transverse rectus abdominis musculocutaneous (TRAM) flap or deep inferior epigastric perforator (DIEP) flap, superficial inferior epigastric vein (SIEV) exists as superficial and independent venous system from deep system. The superficial venous drainage is dominant despite a dominant deep arterial supply in anterior abdominal wall. As TRAM or DIEP flaps began to be widely used for breast reconstruction, venous congestion issue has been arisen. Many clinical series in regard to venous congestion despite patent microvascular anastomosis site were reported. Venous congestion could be divided in two conditions by the area of venous congestion and each condition is from different anatomical causes. First, if venous congestion was shown in whole flap, it is due to the connection between SIEV and vena comitantes of DIEP. Second, if venous congestion is limited in above midline (Hartrampf zone II), it is due to problem in venous midline crossover. In this article, the authors reviewed the role of SIEV in lower abdominal flap based on the various anatomic and clinical studies. The contents are mainly categorized into four main issues; basic anatomy of SIEV, the two cause of venous congestion, connection between SIEV and vena comitantes of DIEP, and midline crossover of SIEV.
Keywords: superficial inferior epigastric vein; venous congestion; deep inferior epigastric perforator flap; transverse rectus abdominis musculocutaneous flap